Phase behavior, formation and characterization of palm-based esters nanoemulsion formulation containing ibuprofen. - Salim, Norazlinaliza; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Kuang, Dzulkefly Abdullah; Basri, Hamidon; Salleh, Abu Bakar (OMICS Publishing Group, 2011)
Palm-based esters, synthesized through enzymatic transesterification of palm oil fractions with oleyl alcohol have potential application in pharmaceutical formulations. The phase behaviour of palm-based esters containing ibuprofen with surfactant of different HLB values was investigated for topical delivery system. The surfactants were Tween 85, Tween 60 and Tween 80, and the palm-based esters were palm oil esters (POEs) and palm kernel oil esters (PKOEs). Ternary phase diagrams of palm-based esters: Ibuprofen/surfactant/water systems were constructed. Three distinct regions were observed in the phase diagrams; isotropic liquid region, L1, liquid crystalline region, Lc and multiphase region, M. Nanoemulsions were prepared spontaneously by the addition of water to oil:ibuprofen/surfactant mixtures based on the ternary phase diagrams constructed. Formulations from the PKOEs:Ibuprofen/Tween 80/water systems were selected due to the presence of large isotropic liquid region, which suggested that this region was suitable to be used in producing nanoemulsions. Particle size analysis showed that the mean particle sizes of these formulations ranged from 10 nm to 70 nm. Zeta potential analysis for all formulations showed negative values from -4 to -8 mV. Stability studies showed that, after 4 h of stirring at room temperature (25°C), the formulations were stable under centrifugation test at 4000 rpm for 15 min. Stability under different storage temperature showed that at 25°C, the four formulations, F1, F2, F3 and F4 were stable with no phase separation for the duration of 1 month. However, when these formulations were stored at 45°C and 4°C, respectively, only F3 and F4 were observed to be stable. These two formulations have the potential to be used for topical delivery of ibuprofen.